2003
DOI: 10.1002/nur.10091
|View full text |Cite
|
Sign up to set email alerts
|

Creating avenues for relative empowerment (CARE): A pilot test of an intervention to improve outcomes of hospitalized elders and family caregivers

Abstract: The purpose of this pilot study was to evaluate the effectiveness of a family caregiver-focused intervention program (CARE) on the outcomes of hospitalized elders and their family caregivers. A randomized clinical trial was conducted with 49 family caregivers of hospitalized elders in a university medical center in upstate New York. Driven by self-regulation and role theories, the two-phase CARE program consisted of: (a). a mutual agreement consisting of family caregiving activities during hospitalization; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 37 publications
1
82
0
7
Order By: Relevance
“…26 For example, in neonatal transitional care units, parents reported feeling less anxious after the adoption of family-centered care, lengths of hospital stay were shorter, and rehospitalizations were fewer. 27 However, few specific strategies 16,20 to promote family-centered care in adult units have been published. Thus, although family-centered care sounds beneficial in theory, little evidence is available of ways to operationalize this model of care.…”
Section: Family Needs In Critical Carementioning
confidence: 99%
See 1 more Smart Citation
“…26 For example, in neonatal transitional care units, parents reported feeling less anxious after the adoption of family-centered care, lengths of hospital stay were shorter, and rehospitalizations were fewer. 27 However, few specific strategies 16,20 to promote family-centered care in adult units have been published. Thus, although family-centered care sounds beneficial in theory, little evidence is available of ways to operationalize this model of care.…”
Section: Family Needs In Critical Carementioning
confidence: 99%
“…The mean length of stay was similar at both sites: 2.8 days. Both sites were combined surgical and medical units that did pilot study of 49 family caregivers in the United States, Li et al 20 found that when family caregivers of elderly patients actively participated in the care of the patients in an acute care setting, the patients experienced fewer episodes of confusion and depression after hospitalization. Although the results of these 2 studies are promising, the benefits of including patients' family members in the care of critical care patients have yet to be fully determined.…”
Section: Sample and Settingmentioning
confidence: 99%
“…5,6,9,11 However, further research is necessary to identify barriers to family participation in care and cost-effective strategies to facilitate and support family participation in care. Although researchers in 1 study 19 did report improved outcomes in older patients, increased understanding is needed to integrate the AACN Synergy Model as a framework to identify nursing competencies that can be used to support the integration of patients' family members into the care of acute and critically ill older adults. CCN…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The use of a partnership model improves patients' outcomes by emphasizing a nonhierarchical relationship in an environment of trust and respect for the diversity that a patient and his or her family bring to the experience of being critically ill. 16 Creating Avenues for Relative Empowerment (CARE) offers further strategies to facilitate family members' participation in care. 19 The focus of CARE is to educate family members on the common problems (Table 3) seen in hospitalized older adults and the activities that can reduce or prevent these problems, such as fecal incontinence, acute confusion, or urinary incontinence. This program has been used with family caregivers of hospitalized older adults in New York with the outcome of fewer incidents of acute confusion and depressive symptoms.…”
Section: Strategies To Facilitate Participationmentioning
confidence: 99%
“…Examples of studies in which a placebo-type intervention was used include studies by H. Li et al (2003) and Calfas, Sallis, Oldenburg, and French (1997). H. Li et al (2003) tested a caregiver support program's effectiveness on improving outcomes for hospitalized elders and family caregivers. The control group received a treatment in the same form received by the intervention group (i.e., audiotapes); however, the tapes were focused on messages unrelated to caregiving.…”
Section: Placebo Treatment Modelmentioning
confidence: 99%